PENGGUNAAN MEDIA PAPAN MULTI FUNGSI DALAM MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN MATEMATIKA - Kadullah, Putri; Otaya, Lian Gafar; Djafar, Fatimah (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2024)
AbstractThis research aims to determine the improvement in learning outcomes of class V students at SDN 7 Limboto in the material of the Least Common Multiple and the Greatest Common Factor in Mathematics Subjects. This research method is Class V Action which is carried out in a class to determine the consequences of the action applied to a research subject in that class. The subjects of this research were class V of SDN 7 Limboto, totaling 18 students. The Classroom Action Research (PTK) model that will be carried out refers to the Kemmis and Taggart model which consists of stages, namely: planning, action, observation and reflection. The results of this research indicate that the application of multi-functional board media can improve student learning outcomes in the material on Least Common Multiple and Greatest Common Factor. In the first cycle, the learning outcomes of 8 students who completed were 44.4% in the